Pengaruh Fortifikasi Vitamin A dan Zat Besi Terenkapsulasi pada Tepung Ubi Kayu dan Aplikasinya pada Pembuatan Flakes - Windi Asterini; Sugiyono Sugiyono; Hoerudin Hoerudin; Endang Prangdimurti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Fortification is one of the promising techniques for decreasing micronutrient deficiency problem, particularly in vitamin A and iron cases. This research aimed to investigate the effect of encapsulated vitamin A and iron fortification on cassava flour and its application on flakes product. Cassava flour was fortified with 5.6 mg/kg of encapsulated vitamin A (retinyl palmitate) for a single treatment, and also combined with 31 mg/kg of encapsulated iron (FeSO4.7H20). Non-fortified cassava flour was used as control. Results showed no significant differences in water content (10.09±0.24 – 10.71±1.76) and the cassava flour’s whiteness degree (98.11±0.13 – 98.85±0.12) for each treatment (p> 0.05). However, with iron levels of (7.42±0.09 – 28.20±0.96) and vitamin A of (<0.50±0.00 – 7.19±1.45), the cassava flour was significantly different (p<0.05). An application of fortified cassava flour fortified in flakes product resulted no significant difference in vitamin A amount (13.23±4.24 – 14.66±0.97) and color product (28.29±0.62 – 30.08±0.97) (p>0.05). Furthermore, level of iron and vitamin A in flakes was increased, positively correlated with fortificant concentration. Fortification with combined treatment (vitamin A and iron) reduced bioaccessibility of vitamin A (51.24±1.32), but significantly improved bioaccessibility of iron (77.69±1.45). Based on organoleptic test, all fortified flakes were acceptable ±5 (rather preferred) to be consumed.